THE SATISFACTION OF THE PERSON WITH URINARY RETENTION IN THE USE OF DIFFERENT TYPES OF URINARY CATHETERS (Estima – Brazilian Journal of Enterostomal Therapy, 2021)
Objective: to assess the satisfaction of the person with urinary retention in the face of the use of different types of urinary catheters, as well as to compare and analyze different attributes of these after their use in clean intermittent catheterization (CIC). Method: descriptive exploratory cross-sectional study, developed in a reference clinic in the state of São Paulo, from February to March 2020. The sample consisted of 32 adults registered in the service, and who adopted the CIC as a form of bladder emptying . Data collection was performed through individual interviews using a semi-structured questionnaire. Data were analyzed using descriptive, inferential statistics and categorization of responses to open questions. Results: of the 32 users, 84% were male, with a mean age of 54.16 years, 81% performed the procedure between 1 and 5 years, with a frequency of 4 to 6 times a day (66%). Most respondents (73%) preferred the hydrophilic-coated polyurethane catheter, converging with the percentage of users satisfied with the same catheter. Conclusion: the most satisfying technology is the hydrophiliccoated polyurethane catheter due to several attributes such as lubrication, firmness, packaging, urethral slip, handling, rapid urine clearance and comfort